Strategi Pengurus Masjid Jami Karya Bakti Palembang dalam Meningkatkan Motivasi Jamaah Melaksanakan Salat Subuh Berjamaah - Destriani Destriani; Suryati Suryati; Anang Walian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is first to find out the strategy of the management of the Jami Karya Bakti Palembang mosque in increasing the motivation of the congregation to carry out the congregational dawn prayers, the second to find out the supporting and inhibiting factors of the Jami Karya Bakti mosque management in increasing the motivation of the congregation to carry out the congregational dawn prayers. In this study the authors used a qualitative method with a descriptive approach. Data collection techniques in this study are observation, interviews, and documentation. The results of this study are the strategies adopted by mosque administrators in motivating congregations by holding dawn lectures which are held once a week by inviting speakers from outside the Jami Karya Bakti Palembang environment. The inhibiting factor for the administrators of the Jami Karya Bakti mosque in increasing the motivation for the morning prayers in the congregation at the Jami Karya Bakti mosque is the lack of awareness of the local community to do the congregational dawn prayers due to laziness and the added atmosphere of getting up from sleep is difficult especially since the dawn atmosphere is cold, and it is still dark which makes Pilgrims prefer morning prayers at home. Supporting factors in motivating the congregation to pray at dawn by holding dawn lectures that can make the congregation gain knowledge or spiritual guidance about worship and there is also a dawn movement carried out by the Palembang city government, Mr. Harnojoyo, and there are mosque facilities.